Answered

Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Consider the function [tex]$f(x)=6 \sqrt{x}+10$[/tex] on the interval [tex][1,7][/tex].

1. Find the average or mean slope of the function on this interval.

By the Mean Value Theorem, we know there exists a [tex]$c$[/tex] in the open interval [tex](1,7)[/tex] such that [tex]$f^{\prime}(c)$[/tex] is equal to this mean slope. For this problem, there is only one [tex][tex]$c$[/tex][/tex] that works.

2. Find it.


Sagot :

To solve this problem, let's work through it in a step-by-step manner.

1. Define the function and the interval:
The function given is [tex]\( f(x) = 6\sqrt{x} + 10 \)[/tex]. The interval we are interested in is [tex]\([1, 7]\)[/tex].

2. Compute [tex]\( f(a) \)[/tex] and [tex]\( f(b) \)[/tex]:
We need to evaluate the function at the endpoints of the interval.
- For [tex]\( a = 1 \)[/tex]:
[tex]\[ f(1) = 6\sqrt{1} + 10 = 6 \cdot 1 + 10 = 16 \][/tex]
- For [tex]\( b = 7 \)[/tex]:
[tex]\[ f(7) = 6\sqrt{7} + 10 \][/tex]

3. Compute the mean slope of the function on the interval [tex]\([1, 7]\)[/tex]:
The mean slope is given by:
[tex]\[ \frac{f(b) - f(a)}{b - a} \][/tex]
Substituting the values, we get:
[tex]\[ \frac{(6\sqrt{7} + 10) - 16}{7 - 1} = \frac{6\sqrt{7} + 10 - 16}{6} = \frac{6\sqrt{7} - 6}{6} = \sqrt{7} - 1 \][/tex]

4. Find the derivative of [tex]\( f(x) \)[/tex]:
The derivative of the function [tex]\( f(x) = 6\sqrt{x} + 10 \)[/tex] is:
[tex]\[ f'(x) = \frac{d}{dx} \left( 6\sqrt{x} + 10 \right) = 6 \cdot \frac{1}{2} \cdot x^{-1/2} = \frac{3}{\sqrt{x}} \][/tex]

5. Set the derivative equal to the mean slope to find [tex]\( c \)[/tex]:
According to the Mean Value Theorem, there exists some [tex]\( c \)[/tex] in the open interval [tex]\( (1, 7) \)[/tex] such that [tex]\( f'(c) \)[/tex] is equal to the mean slope. So, we set:
[tex]\[ f'(c) = \sqrt{7} - 1 \][/tex]
[tex]\[ \frac{3}{\sqrt{c}} = \sqrt{7} - 1 \][/tex]

6. Solve for [tex]\( c \)[/tex]:
Rearrange the equation to solve for [tex]\( c \)[/tex]:
[tex]\[ 3 = (\sqrt{7} - 1)\sqrt{c} \][/tex]
[tex]\[ \sqrt{c} = \frac{3}{\sqrt{7} - 1} \][/tex]

Squaring both sides to solve for [tex]\( c \)[/tex]:
[tex]\[ c = \left( \frac{3}{\sqrt{7} - 1} \right)^2 \][/tex]

7. Simplify the expression for [tex]\( c \)[/tex]:
Simplify the right side of the equation:
[tex]\[ c = \left( \frac{3}{\sqrt{7} - 1} \right)^2 = \frac{9}{(\sqrt{7} - 1)^2} \][/tex]

Therefore, the value of [tex]\( c \)[/tex] in the interval [tex]\( (1, 7) \)[/tex] that satisfies the Mean Value Theorem is:
[tex]\[ c = \frac{9}{(\sqrt{7} - 1)^2} \][/tex]

Thus, we have found that the [tex]\( c \)[/tex] such that [tex]\( f'(c) = \sqrt{7} - 1 \)[/tex] within the interval [tex]\( (1, 7) \)[/tex] is [tex]\( \frac{9}{(\sqrt{7} - 1)^2} \)[/tex].